Synergies in urban networks: complementarities and competitiveness - Santos, Iann Dellano da Silva; Castilho, Denis (Geografares, 2024)
Regarding the diversity and complexity of urban networks, the relations between complementarity and competitiveness can be examined to understand not only the particularity of these networks, but also the role they play in production relations and the mechanisms that validate their dynamics and meanings. In an attempt to understand these interfaces, this exploratory-bibliographical article questions the combination between them and their predominance. In addition to the dualism or traditional separation between pairs, a synergy is observed that, depending on the predominance, can trigger relative stratifications or instabilities in the regional urban network. In a broad and utopian sense, through the synergies governed by corporate market systems and according to the set of strategies coordinated on a regional scale, complementary relations can reach levels of cooperation and horizontal exchanges. In these terms, synergy presents important ruptures in the hierarchical and unequal pattern of urban networks. However, it is considered that dialectic between competitiveness and complementarity refers to the need for sine qua non investigation of each case.